Evaluating Hydrocolloids of Sida Acuta as Sustained Release Matrix for Ibuprofen Tablet (Global Journal of Medical Research, 2020)
Abstract not found
Keywords: Sida acuta gum; ibuprofen; sustained release; matrix tablet; guar gum